Penyuluhan pembuatan ovitrap terhadap pengetahuan dan sikap ibu rumah tangga dalam pengendalian DBD - Melati Rias Susanto; Ridwan Ridwan; Pitri Noviadi (Health Sciences and Pharmacy Journal, 2022)
Dengue hemorrhagic fever (DHF) is a disease transmitted by the bite of the Aedes aegypti that contains the dengue. Dengue hemorrhagic fever can be controlled by making ovitrap or mosquito egg trap. Good knowledge and attitudes in controlling dengue hemorrhagic fever formed by counseling on the manufacture of ovitrap. This study is to determine the effect of counseling on making ovitrap on the knowledge and attitude of housewife in controlling dengue hemorrhagic fever in Tanjung Batu Timur Village, Ogan Ilir Regency in 2022. This study used quantitative methods. The type of research used was a quasi-experimental one group sample. Data collection techniques were through observation, interviews and group division. This research was conducted in March-May 2022. The population of this research study was housewife in Tanjung Batu Timur Village, Tanjung Batu District, Ogan Ilir Regency. The  samples were 101 people. Data analysis used the Wilcoxon Test. The result of this research showed that knowledge and attitude of housewife havesignificant results with p (0.000) so that there was a significant difference between pretest and posttest after counseling. The conclusion in this study was that there was an effect of counseling on making ovitrap on the knowledge and attitude of housewife in controlling dengue hemorrhagic fever in Tanjung Batu Timur Village, Ogan Ilir Regency in 2022.